1990
DOI: 10.1038/bjc.1990.307
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oestrogens induce the secretion of active transforming growth factor beta from human fetal fibroblasts

Abstract: (Green & Leake, 1987). These cells were allowed to grow for 3 days, until approximately 50% confluent. The medium was then discarded and the cell monolayers washed twice with warm phosphate-buffered saline. The cells were then incubated with 50 ml of a defined medium consisting of phenol red-free MEM, supplemented with 2 mM L-glutamine, MEM vitamins, 5 yg ml-1 bovine insulin, 5 jig ml' human transferrin, 2 lag ml-' bovine fibronectin, 10 ng ml-' bovine epidermal growth factor, 1 nM sodium selenite and 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
6

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(91 citation statements)
references
References 24 publications
2
83
0
6
Order By: Relevance
“…Thus, tamoxifen was found to be a potent activator of ER mediated induction of promoters regulated by AP-1 sites in a cell type speci®c pattern; with agonism only occurring in cell lines of uterine but not of breast origin (Webb et al, 1995). Alternatively tamoxifen may act by an oestrogen independent mechanism as has been proposed for its stimulation of TGFb in vitro in human fetal ®broblasts and in vivo in human breast tissue stroma (Colletta et al, 1990;Butta et al, 1992).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, tamoxifen was found to be a potent activator of ER mediated induction of promoters regulated by AP-1 sites in a cell type speci®c pattern; with agonism only occurring in cell lines of uterine but not of breast origin (Webb et al, 1995). Alternatively tamoxifen may act by an oestrogen independent mechanism as has been proposed for its stimulation of TGFb in vitro in human fetal ®broblasts and in vivo in human breast tissue stroma (Colletta et al, 1990;Butta et al, 1992).…”
Section: Introductionmentioning
confidence: 95%
“…LAP regulates TGF-,B activity in cell culture (Gentry and Nash, 1990) and in vivo (Wallick et al, 1990) and influences the distribution of TGF-,B in the organism, increasing the halflife of the growth factor 50-fold . Latent TGF-f circulates in plasma at concentrations well above those necessary for TGF-f to elicit biological activity (Danielpour et al, 1989 (Knabbe et al, 1987;Glick et al, 1989;Oreffo et al, 1989;Colletta et al, 1990;Twardzik et al, 1990;Flaumenhaft et al, unpublished data). Activation of latent TGF-#1 also occurs in homotypic cultures of erythroleukemia cell lines (Piao et al, 1990) (Jullien et al, 1989;Pfeilschifter et al, 1990).…”
Section: Regulation In Time and Spacementioning
confidence: 99%
“…In addition it has been shown that a fibroblast-derived polypeptide from malignant breast tumours cause a significant increase of epithelial 17-beta-estradiol dehydrogenase activity, thereby increasing the local concentration of estradiol (Adams et al, 1988b). Moreover, exposure of human foetal fibroblasts to antioestrogens induces the secretion of active transforming growth factor-beta, despite the absence of oestrogen receptor within these cells (Colletta et al, 1990).…”
mentioning
confidence: 99%